Effects of different small-sided games on psychological responses and technical activities in young female basketball players - Gok, Yagmur; Suel, Emin; Soylu, Yusuf (Acta Gymnica, 2023)
Background: Although small-sided games (SSG) have been a popular method recently, the number of studies on female athletes is limited.Objective: This study investigated the effects of basketball-specific 2vs2, 3vs3 and 4vs4 SSG on psychological and technical responses. Methods: Eighteen young female basketball players with an age of 15.6 ± 0.7 years, a height of 175.0 ± 4.9 cm, a basketball experience of 5.6 ± 0.7 years, and a body mass index of 20.8 ± 1.1 kg/m2 participated in the study. Anthropometric measurements and Yo-Yo Intermittent Recovery Test 1 were conducted. Rating of perceived exertion (RPE), enjoyment of physical activity (PACES-S), mental fatigue and emotion responses of the players were assessed after each bout in basketball-specific 2vs2, 3vs3 and 4vs4 SSG. Results: Significant differences in RPE, PACES-S and emotional responses were found for 2vs2, 3vs3 and 4vs4 games (p < .05). In addition to these results, 2vs2 and 3vs3 formats revealed significant differences in rebounding, successful shots, unsuccessful shots and successful passes in the technical responses (p < .05). Conclusions: The findings show that changing game forms can improve player experiences and encourage higher levels of physical activity, enjoyment, emotional responses, and technical ability. Further research could explore additional variables, such as tactical decision-making, cognitive load, and long-term effects of using different game forms.
Keywords: Motor Skills; týmové sporty; Female; ženské pohlaví; motorické dovednosti; Adolescent; pohybová aktivita; basketbal; Athletic Performance; lidé; cvičení; psychická odolnost; Basketball; Team Sports; sportovní výkon; Motor Activity; Exercise; Resilience, Psychological; mladiství; Humans